Entrepreneurship in Islam and the Prophet's Successful Business Strategy - M. Syafi’i; Alif Basman Amrullah; Endang Trisiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
. In Islam, Entrepreneurship is considered a good deed and is recommended to be done. Entrepreneurship in Islam must be carried out with strategic principles as taught by the Prophet Muhammad SAW, namely not harming others and must also be carried out in a responsible manner and utilizing existing resources as best as possible. The principles of the Prophet Muhammad include: honest, loyal, fair in the business world. never make his customers complain, keep promises and deliver the ordered goods on time, always show a great sense of responsibility and high integrity with anyone. His reputation as an honest and true trader has been widely known since he was young before marriage and old age after marriage, this is precisely what is often practiced by the Prophet and his followers, successEntrepreneurship suasai in Islam